A proposal for the motion analysis method of skiing turn by measurement of orientation and gliding trajectory - Hirose, K.; Doki, H. (Procedia Engineering, 2011)
This paper proposes the motion analysis method on skiing turn by the measurement system of orientation and gliding trajectory. The orientation measurement system that consists of inertial and magnetic field sensor measures angular velocity, acceleration and magnetic field, on the other hand the gliding trajectory measurement system that consists of the GPS receiver measures latitude, longitude and altitude. The 3D orientation of skier's body segments and the 3D gliding trajectory on skiing turn are estimated using sensor fusion and the information measured by the orientation measurement systems and the gliding trajectory measurement system attached to skier. The 3D gliding velocity on skiing turn is estimated with the 3D gliding trajectory. The measurement experiment has been conducted by the skier attached the measurement systems on an actual snow field. The joint angle has indicated the gliding form in skidding and carving turn, the gliding trajectory has visualized clearly the difference in moving distance between skidding turn and carving turn. Furthermore, the gliding velocity relative to skier's coordinate has perceived the different period and the effect of side skidding on these two turns. The experimental results have indicated quantitatively the ever-changing state of skier. The major features of skiing turn can be analyzed by the proposed method, which can use as an effective method for suggesting more ideal turning form, the skill rating, the prevention of disorder and injury from skiing.